OPTIMIZATION OF EXTRACTION WITH SOLVENT VARIATION BASED ON TOTAL FLAVONOID CONTENT IN WUNGU LEAVES (Graptophyllum pictum (L.) Griff): A LITERATURE REVIEW - Subeno, Setia; Makkiyah, Feda (The Health Researcher's Journal, 2024)
There are many studies analyzing the flavonoid content based on the total flavonoid content (TFC) of wungu leaves through the extraction process with different extraction solvents. So, this review using literature review methodology is aimed to find out the type of extraction solvent that has the most optimum condition based on the highest TFC. The databases for collecting data involved PubMed, Scopus, and Google Scholar. Temporary, the results based on some previous studies vary greatly. Two of four selected articles showed that the highest TFC was found in semi-polar solvents; ethyl acetate and acetone. It is suspected that the samples contain more aglycones (a subtype of flavonoids) that can be soluble in semi-polar solvents. Whereas, the two others showed that the nonpolar solvent (hexane) had the highest TFC. It is suspected that the samples contain more subtypes of flavonoids called isoflavones, flavanones, flavones, and flavonols that can be soluble in nonpolar solvents. To get the appropriate and best standardized extract of wungu leaves, re-examination of this optimization based on the highest TFC in further research is necessary by using different extraction solvents that are equally polar like water, methanol, and ethanol; because the flavonoids as secondary metabolites in plants are basically polar.